TINDAK TUTUR DIREKTIF DALAM PIDATO PRESIDEN PRABOWO: SENTILAN TERHADAP PEJABAT YANG HANYA FOTO-FOTO SAAT MENGUNJUNGI LOKASI BENCANA BANJIR DI SUMATERA - Novi Fitriani; Zuraida Khairani; Susanti Marisya (STKIP Pesisir Selatan, 2025)
Speeches are a more formal and focused means of communication, allowing the audience to listen more intently to what the speaker is saying. Speech acts are an important aspect of language study. This study aims to describe and analyze the forms of directive speech acts used by President Prabowo in his speeches. The method used is a descriptive qualitative method with a listening and note-taking technique on the research data in the form of utterances obtained from videos of President Prabowo's speeches uploaded to the YouTube platform. The results of the study indicate that the dominant directive speech acts that appear are questions, orders, and prohibitions on the use of these speeches aimed at state officials to take concrete action in disaster management. These directive speech acts function as a tool of social control, strengthening leadership ethics, and a means of affirming the president's stance on symbolic practices that do not directly impact disaster victims.